Effect of Circular Stapler Diameter on Anastomotic Leakage Rate and Stenosis After Open Total Gastrectomy With Esophagojejunostomy - Anke Mittelstädt, Dr. med.; Helena Reitberger, Dr. med.; Julia Fleischmann, Dr. med. dent.; Moustafa Elshafei, Dr. med.; Maximilian Brunner, PD Dr. med.; Anna Anthuber; Christian Krautz, PD Dr. med.; Marianna Lucio, Dr.; Susanne Merkel, Prof. Dr. med.; Robert Grützmann, Prof. Dr. > med.; Georg F. Weber, Prof. Dr. med. (Annals of Surgery Open, 2022)
Background:. Anastomotic leakage (AL) and stenosis (AS) are two of the most severe postoperative complications after total gastrectomy with esophagojejunostomy. The stapler diameter can be chosen by the surgeon. Therefore, this study aims to assess the correlation between the stapler size as main independent variable as well as other different risk factors and AL and AS. Methods:. We conducted a retrospective analysis of data from 356 patients who underwent open total gastrectomy between 2000 and 2018, mostly due to gastric cancer (96.9%). After propensity score matching the outcome parameters AL and AS were compared between the two stapler size groups. We also assessed different risk factors for AL and AS in cancer patients using multivariate analysis. Results:. Small circular stapler diameter (21/25 mm; n = 147 vs 28/29/31 mm; n = 209) was identified as a significant risk factor for the occurrence of AL (10% vs 4% for smaller vs larger staplers; P = 0.042). In multivariate analysis for the occurrence of AL an ASA score ≥ 3 could be identified as a risk factor (OR 2.85; 95% CI = 1.13–7.15; P = 0.026). Additionally, smaller stapler size could be identified as a risk factor for AS (OR small 1.00, OR large 0.24; 95% CI: 0.06–0.97; P = 0.045). AL was associated with lower survival (18.1 vs 38.16 months; P = 0.0119). Conclusion:. The application of a larger circular stapler for esophagojejunostomy in open total gastrectomy shows significantly lower rates of AL and stenosis. Therefore, the largest possible stapler diameter should be applied.